2013
DOI: 10.1080/09672567.2013.792375
|View full text |Cite
|
Sign up to set email alerts
|

Adam Smith on the subordination of wage-earners in the commercial society

Abstract: International audienceAdam Smith's discourse on wage labour is both original for its time and complex. While Smith indisputably considered the substitution of serfdom by wage labour as an improvement in both opulence and independence, we argue that he nevertheless saw the wage relationship as one founded on subordination. We then cast light on the material factors and symbolic mechanisms which, in his writings, explain how and why the worker agrees to this subordination. Finally, we endeavour to show that Smit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The importance of rhetoric for understanding Smith’s work has been increasingly acknowledged over the last couple of decades. Some scholars have investigated if, and how, Smith’s rhetoric shows up in his TMS (Griswold 1991; Brown 1994; McKenna 2005; Hanley 2009), or in specific parts or topics of the WN (Endres 1991; Gore 2011; Peaucelle 2012; Herzog 2013; Dellemotte and Walraevens 2015). More general statements about the rhetoric of Smith’s WN can be found in Brown (1994) and Fleischacker (2004, ch.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of rhetoric for understanding Smith’s work has been increasingly acknowledged over the last couple of decades. Some scholars have investigated if, and how, Smith’s rhetoric shows up in his TMS (Griswold 1991; Brown 1994; McKenna 2005; Hanley 2009), or in specific parts or topics of the WN (Endres 1991; Gore 2011; Peaucelle 2012; Herzog 2013; Dellemotte and Walraevens 2015). More general statements about the rhetoric of Smith’s WN can be found in Brown (1994) and Fleischacker (2004, ch.…”
Section: Introductionmentioning
confidence: 99%
“…We agree here withMuller (1993),Brown (1994),and Fleischacker (2004)). Previous research on the rhetorical parts of the WN can be found inEndres (1991) who turns his attention to chapter 5 of book IV of the WN and there in particular bounties, inDellemotte & Walraevens (2013) who show that Smith's description of the disputes between laborers and capital owners in chapter 8 of Book I is meant to elicit the sympathy of his readers towards the former, inPeaucelle (2012) who identifies the rhetorical tricks used to win the readers' goodwill in the first chapter of the WN on the division of labour, and inHerzog (2013) who analyzes the rhetoric of opening sections of the WN. Fleischacker (2004; see in particular pp.…”
mentioning
confidence: 99%